2011
DOI: 10.1038/nature10495
|View full text |Cite
|
Sign up to set email alerts
|

CTCF-binding elements mediate control of V(D)J recombination

Abstract: Immunoglobulin heavy chain (IgH) variable region exons are assembled from VH, D and JH gene segments in developing B lymphocytes. Within the 2.7 megabase (Mb) mouse IgH locus (IgH), V(D)J recombination is regulated to ensure specific and diverse antibody repertoires. Herein, we report a key IgH V(D)J recombination regulatory region, termed InterGenic Control Region-1 (IGCR1), that lies between the VH and D clusters. Functionally, IGCR1 employs CTCF looping/insulator factor binding elements and, correspondingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
361
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(383 citation statements)
references
References 54 publications
17
361
0
Order By: Relevance
“…Although not directly related to the control of gene expression, the case of the Igh locus provides another interesting example of interactions between noncoding elements (Guo et al, 2011). This genomic region contains multiple CTCF insulator elements whose interactions are necessary to produce correct V(D)J rearrangements (Guo et al, 2011).…”
Section: Interactions Between Regulatory Elementsmentioning
confidence: 99%
“…Although not directly related to the control of gene expression, the case of the Igh locus provides another interesting example of interactions between noncoding elements (Guo et al, 2011). This genomic region contains multiple CTCF insulator elements whose interactions are necessary to produce correct V(D)J rearrangements (Guo et al, 2011).…”
Section: Interactions Between Regulatory Elementsmentioning
confidence: 99%
“…Long-range interactions and locus conformations are determined in large part by CCCTC-binding factor (CTCF) and cohesin, factors that bind numerous sites throughout the mammalian genome forming loops containing the intervening DNA (16). With regard to AgR loci, deletion of CTCF, its binding sites, or essential cohesin subunits disrupt spatial interactions at Igk, Igh, and Tcra, respectively, and perturb V to (D)J recombination (17)(18)(19)(20).…”
Section: Significancementioning
confidence: 99%
“…19 Interestingly, it was demonstrated that cooperation between T-bet and Ctcf is required for Th1 cell-specific expression of IFN-c. 20 In addition, Ctcf also plays a role in the regulation of V(D)J recombination events and V gene usage at the Ig H and L chain loci in B cells. 21,22 The role of Ctcf in development and function of myeloid cells in vivo has not been investigated. Here, we used the transgenic Cre-loxP system to generate conditional myeloid-specific Ctcf-knockout mice, allowing analysis of the role of Ctcf in the development and function of macrophages in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%